2005
DOI: 10.1079/bjn20041303
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in support of a role for plant-mediated proteolysis in the rumens of grazing animals

Abstract: The present work aimed to differentiate between proteolytic activities of plants and micro-organisms during the incubation of grass in cattle rumens. Freshly cut ryegrass was placed in bags of varying permeability and incubated for 16 h in the rumens of dairy cows that had previously grazed a ryegrass sward, supplemented with 4 kg dairy concentrate daily. Woven polyester bags (50 mm pore size) permitted direct access of the micro-organisms and rumen fluid enzymes to the plant material. The polythene was imperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…; Kingston‐Smith et al. ) and hence current efforts to mitigate impact of ruminant farming through selection of improved forage genotypes. Shaw () demonstrated that Fg was significantly more stable under rumen‐like conditions than Lolium species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Kingston‐Smith et al. ) and hence current efforts to mitigate impact of ruminant farming through selection of improved forage genotypes. Shaw () demonstrated that Fg was significantly more stable under rumen‐like conditions than Lolium species.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive nitrogen loss to the environment due to poor incorporation of dietary N by ruminants causes both pollution of ground water and contributes to nitrous oxide production. This is due to excessive proteolysis in the rumen, for which plant-mediated proteolysis is a contributory factor (Zhu et al 1999 ;Wallace et al 2001 ;Kingston-Smith et al 2005 ) and hence current efforts to mitigate impact of ruminant farming through selection of improved forage genotypes. Shaw ( 2006 ) demonstrated that Fg was signifi cantly more stable under rumen-like conditions than Lolium species.…”
Section: Discussionmentioning
confidence: 99%
“…However, how the plant cells die and how they use their endogenous constituents to prevent death has an impact on nutrient availability for the ruminal microorganisms. For instance, it has been demonstrated that exposing forage species to the ruminal conditions of heat and anoxia in the absence of a microbial inoculum is sufficient to promote rapid degradation of plant protein by the plant's own proteases (61)(62)(63) . Stress-induced proteolysis in plants is a phenomenon that has been widely reported for biotic and abiotic stresses (64)(65)(66)(67) .…”
Section: Plant-based Solutionsmentioning
confidence: 99%
“…The aim of probiotic and prebiotic inclusions into the diet are to increase beneficial gut bacteria and their activities, thus generating benefits to human health. These benefits include protection from gastroenteritis by pathogen inhibition [1], an improved tolerance to lactose [2], toxins [3] and cholesterol reduction [4], vitamin synthesis [3], improved mineral bioavailability [5], potential protection from bowel cancer [6-8], reduced symptoms of irritable bowel syndrome [9], improved digestion, gut function [10] and immune regulation [11]. …”
Section: Introductionmentioning
confidence: 99%